Structural probing of off-target G protein-coupled receptor activities within a series of adenosine/adenine congeners. - Silvia Paoletta; Dilip K Tosh; Daniela Salvemini; Kenneth A Jacobson (PLoS ONE)
We studied patterns of off-target receptor interactions, mostly at G protein-coupled receptors (GPCRs) in the µM range, of nucleoside derivatives that are highly engineered for nM interaction with adenosine receptors (ARs). Because of the considerable interest of using AR ligands for treating diseases of the CNS, we used the Psychoactive Drug Screening Program (PDSP) for probing promiscuity of these adenosine/adenine congeners at 41 diverse receptors, channels and a transporter. The step-wise truncation of rigidified, trisubstituted (at N6, C2, and 5' positions) nucleosides revealed unanticipated interactions mainly with biogenic amine receptors, such as adrenergic receptors and serotonergic receptors, with affinities as high as 61 nM. The unmasking of consistent sets of structure activity relationship (SAR) at novel sites suggested similarities between receptor families in molecular recognition. Extensive molecular modeling of the GPCRs affected suggested binding modes of the ligands that supported the patterns of SAR at individual receptors. In some cases, the ligand docking mode closely resembled AR binding and in other cases the ligand assumed different orientations. The recognition patterns for different GPCRs were clustered according to which substituent groups were tolerated and explained in light of the complementarity with the receptor binding site. Thus, some likely off-target interactions, a concern for secondary drug effects, can be predicted for analogues of this set of substructures, aiding the design of additional structural analogues that either eliminate or accentuate certain off-target activities. Moreover, similar analyses could be performed for unrelated structural families for other GPCRs.